2019
DOI: 10.1093/mnras/stz976
|View full text |Cite
|
Sign up to set email alerts
|

The evolutionary status of Cataclysmic Variables: eclipse modelling of 15 systems

Abstract: We present measurements of the component masses in 15 Cataclysmic Variables (CVs) -6 new estimates and 9 improved estimates. We provide new calibrations of the relationship between superhump period excess and mass ratio, and use this relation to estimate donor star masses for 225 superhumping CVs. With an increased sample of donor masses we revisit the implications for CV evolution. We confirm the high mass of white dwarfs in CVs, but find no trend in white dwarf mass with orbital period. We argue for a revisi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 112 publications
4
63
0
1
Order By: Relevance
“…See also the review by Zortovic and Schreiber in this special issue. The period minimum in the CV distribution is 65 min as calculated theoretically (Kolb and Baraffe, 1999;Howell et al, 2001), however observations indicate a minimum period of 79.6±0.2 min (McAllister et al, 2019, and references therein). The discrepancies in the observed and theoretical, minimum period and space density are still open problems in the current understanding of the CV evolution together with the WD mass problem.…”
Section: Nonmagnetic Cataclysmic Variablesmentioning
confidence: 65%
“…See also the review by Zortovic and Schreiber in this special issue. The period minimum in the CV distribution is 65 min as calculated theoretically (Kolb and Baraffe, 1999;Howell et al, 2001), however observations indicate a minimum period of 79.6±0.2 min (McAllister et al, 2019, and references therein). The discrepancies in the observed and theoretical, minimum period and space density are still open problems in the current understanding of the CV evolution together with the WD mass problem.…”
Section: Nonmagnetic Cataclysmic Variablesmentioning
confidence: 65%
“…Previous studies (e.g. Wood et al 1986;McAllister et al 2019) find that the accretion disk is only partially obscured at maximum eclipse depth during quiescence. However, we find a 1:1 correlation between eclipse depth and out-of-eclipse flux for Z Cha during quiescence in Sector 6.…”
Section: Hysteresis In Eclipse Depth/out-of-eclipse Flux Spacementioning
confidence: 88%
“…In so-called 'dwarf-nova' AWDs, changes in the flow rate through the accretion disk can take place in the form of 'outbursts ' (e.g. Warner 1976;Meyer & Meyer-Hofmeister 1984): dramatic E-mail: James.Court@ttu.edu increases in luminosity which persist for timescales of a few days and recur on timescales of weeks to years (e.g. Cannizzo et al 1988).…”
Section: Introductionmentioning
confidence: 99%
“…The location of the orbital period minimum has been another discrepancy between models and observations. Theoretical simulations where gravitational radiation is assumed to be the only angular momentum loss mechanism for fully convective donor stars predict a minimum orbital period of ∼ 65 − 70 min (Kolb, 1993;Kolb & Baraffe, 1999;Howell et al, 2001;Goliasch & Nelson, 2015;Kalomeni et al, 2016), while the observed value is ∼ 76 − 82 min (Knigge, 2006;Knigge et al, 2011;McAllister et al, 2019). However, the simulated location of the orbital period minimum could be shifted towards larger periods if an additional source of angular momentum loss, apart from gravitational radiation, is present below the gap (Kolb & Baraffe, 1999;Knigge et al, 2011).…”
Section: Theoretical Predictions Versus Observationsmentioning
confidence: 99%
“…This survey revealed a much larger fraction of CVs with short periods compared with any previous CV sample and an accumulation of systems close to the shortest periods ). In addition, McAllister et al (2019) recently estimated donor star masses for a sample of 225 CVs showing superhump phenomena (Papaloizou & Pringle, 1979) and found that 30 per cent are likely to be period bouncers with brown dwarf donors. However, Pala et al (2019) found a fraction of only 5 per cent of period bouncers in a volume limited sample of CVs.…”
Section: Theoretical Predictions Versus Observationsmentioning
confidence: 99%